PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS X AKUNTANSI SMK TARUNA SATRIA PEKANBARU - Suzana, Suzana; Kartini, Kartini; Solfitri, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research is classroom action research that aims to improve learning process and to increase student mathematics achievement with applied the learning model of Problem Based Learning. The subject of this research was student of class X Akuntansi SMK Taruna Satria Pekanbaru in second academic years 2018/2019, which are 30 students, consist of nine boys and 21 girls. The research consist of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. The instruments of data collection in this research is observation sheets and students mathematic tests. The observation sheets was analyzed by narrative descriptive analysis technique, and the students mathematic tests was analyzed by descriptive statistical analysis technique. The qualitative descriptive showed an improvement of learning process prior to the action on the first and second cycle. Most of students were very confidenced and actived in learning process. The results of this study indicate the number of students who reached Minimum Mastery Criteria increase from basic score to UH-I and UH-II. The results of this research showed an increasing number of students learning mathematics about knowledge of the basic score (26,67%) to the first UH-I (56,67%) to the UH-II (93,33%) thus it can be concluded that the implementation of Problem Based Learning model can improve learning process and increase mathematics achievement from the students at class X Akuntansi SMK Taruna Satria Pekanbaru in second academic years 2018/2019 for the linear program.Key Words: Students’ Mathematic Achievement, Problem Based Learning, Class Action Research